Workshop on Marketing and Development of Processed Product in Kampung Susu Lawu, Magetan, East Java - Erris Kusumawidjaya; Agoes Tinus Lis Indrianto; Rean Mitasari; Verina Wijaya; Christy Widyawati (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
Kampung Susu Lawu in Magetan, East Java, shows significant potential in developing micro, small, and medium enterprises (MSMEs) through processed milk and chips products. Despite having adequate infrastructure, local communities face challenges in diversifying products and increasing sales turnover. This study aims to overcome these obstacles through a structured mentoring program, including training in processing technology and digital marketing strategies. The method used in this community service is participatory, actively involving the community in every stage of product development. Training in processing technology and digital marketing has succeeded in significantly increasing the knowledge and skills of participants. The results of the study show that mentoring has not only succeeded in improving product quality and marketing capacity, but has also had a positive impact on the income and standard of living of the Kampung Susu Lawu community. However, several challenges such as resistance to change and limited access to technology still need to be overcome. To ensure long-term sustainability, stronger collaboration with external stakeholders and policy support that supports wider market access are important. This study emphasizes the importance of a participatory approach and ongoing support in community empowerment to support local economic development.